ANALYSIS OF PHENOLIC AND FLAVONOIDS OF WILD EPHEDRA ALATA PLANT EXTRACTS BY LC/PDA AND LC/MS AND THEIR ANTIOXIDANT ACTIVITY - Al-Rimawi, Fuad; Abu-Lafi, Saleh; Abbadi, Jehad; Alamarneh, Ayman A.A.; Sawahreh, Raneen A.; Odeh, Imad (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Ephedra is among Palestinian medicinal plants that are traditionally used in folkloric medicine fortreating many diseases. Ephedra is known to have antibacterial and antioxidant effects. The goal of this study is toevaluate the antioxidant activity of different extracts from the Ephedra alata plant growing wild in Palestine, and toanalyze their phenolic and flavonoid constituents by HPLC/PDA and HPLC/MS.Materials and Methods: Samples of the Ephedra alata plant grown wild in Palestine were extracted with threedifferent solvents namely, 100% water, 80% ethanol, and 100% ethanol. The extracts were analyzed for their totalphenolic content (TPC), total flavonoid content (TFC), antioxidant activity (AA), as well as phenolic and flavonoidscontent by HPLC/PDA/MS.Results: The results revealed that the polarity of the extraction solvent affects the TPC, TFC, and AA of extracts. Itwas found that both TPC and AA are highest for plant extracted with 80% ethanol, followed by 100% ethanol, andfinally with 100% water. TFC however was highest in the following order: 100% ethanol > 80% ethanol > water.Pearson correlation indicated that there is a significant correlation between AA and TPC, but there is no correlationbetween AA and TFC. Simultaneous HPLC-PDA and UHPLC-MS analysis of the ethanolic plant extracts revealed thepresence of Luteolin-7-O-glucuronide flavone, Myricetin 3-rhamnoside and some other major polyphenoliccompounds that share myricetin skeleton.Conclusion Ephedra alata extract is rich in potent falvonoid glycosidic compounds as revealed by their similaroverlaid UV-Vis spectra and UHPLC-MS results. On the basis of these findings, it is concluded that Ephedra alataconstitutes a natural source of potent antioxidants that may prevent many diseases and could be potentially used infood, cosmetics, and pharmaceutical products.